A New Formulation of an Old Drug: A Potential New Therapy in the Management of Oral cGvHD. Issue 8 (November 2016) - Bertelli, Luca; Di Nardo, Giovanni; Zama, Daniele; Bardasi, Giulia; Morello, William; Masetti, Riccardo; Belotti, Tamara; Forchielli, Maria Luisa; Prete, Arcangelo; Pession, Andrea
Abstract : Oral chronic graft versus host disease (cGVHD) is often refractory to systemic therapies. Additional topical treatment is commonly required. The potency of the agent, the vehicle and formulation in which it is delivered are all critical factors in determining the effectiveness of topical therapies. High potency of budesonide, combined with its very low bioavailability when absorbed through mucosal surfaces, increased the potential role in topical application for oral cGVHD. Viscous formulation increases mucosal contact time resulting in a greater decrease in mucosal inflammation. This short communication suggests that oral viscous budesonide should be considered as a potential new therapy in the management of oral cGVHD.